Language Attitudes and Classroom Language Performance of an Indonesian-Filipino Student in an Indonesian Elementary School - Bella Oktariana; Luh Putu Artini; Ni Luh Putu Sri Adnyani (Cetta: Jurnal Ilmu Pendidikan, 2026)
The existence of bilingualism in formal education requires students to develop a deeper understanding of language attitudes and the process of linguistic adaptation. This study aims to explore language attitudes, linguistic adaptation, and bilingual language performance among students from mixed Indonesian-Filipino families within the context of Indonesian education. This research employs a qualitative approach, with data collected through in-depth interviews, direct observations, reflective anecdotal notes, and document analysis of student learning outcomes. The validity of the data is ensured through source and technique triangulation. The collected data were analyzed using the Miles and Huberman model, namely data reduction, data display, and conclusion drawing. The results of the study found that students demonstrated positive attitudes toward both languages, which were influenced by the intensity of language exposure, affective factors, linguistic competence, learning environment, instructional support, and personal learning preferences. Regarding academic achievement in the classroom, students’ reading ability was stronger than their speaking ability, with English proficiency consistently more dominant and higher than Indonesian language proficiency. The main challenges affecting effective language use in the classroom include affective barriers, vocabulary limitations, communication difficulties, and the need for scaffolding in spontaneous communication. In conclusion, multicultural backgrounds contribute to strong English language preferences due to dominant exposure, while the development of Indonesian language proficiency is constrained by vocabulary limitations and confidence-related challenges. Therefore, students need adaptive instructional support, an inclusive affective approach, and interactive learning stimulation to strengthen their speaking confidence and expand their mastery of Indonesian vocabulary.